2008
DOI: 10.7202/018095ar
|View full text |Cite
|
Sign up to set email alerts
|

Les relations école - familles immigrées au Québec et en Catalogne

Abstract: Cet article est une synthèse faite sur les relations école-familles immigrées au Québec et en Catalogne. Les auteures ont une longue expérience de collaboration dans ce domaine. Sont présentées les difficultés réelles ou projetées de ces relations. Les recherches recensées explorent la problématique selon des enjeux sociétaux relatifs à la diversité ethnoculturelle dans les deux contextes (en particulier à l’école), du point de vue du profil socioéconomique des familles, à travers la réalité de la communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
2
0
6
Order By: Relevance
“…Since the publication of the report and also during the hearings of the Consultation Commission on Accommodation Practices Related to Cultural Differences, it also became evident that a majority of Muslim families are well prepared to live in a pluralist society and actively participate to educational institutions where various rights and diversities of different natures are balanced through the lens of democratic values and civic participation (Kanouté and Vatz Laaroussi 2008;Kanouté and Calvet 2008). Even among the more pious or orthodox sectors of the community, this commitment is also largely shared as exemplified by the practices of various private Muslim schools (Sawaf and Abu Hijleh 2008).…”
Section: Toward Mutual Adaptationmentioning
confidence: 98%
“…Since the publication of the report and also during the hearings of the Consultation Commission on Accommodation Practices Related to Cultural Differences, it also became evident that a majority of Muslim families are well prepared to live in a pluralist society and actively participate to educational institutions where various rights and diversities of different natures are balanced through the lens of democratic values and civic participation (Kanouté and Vatz Laaroussi 2008;Kanouté and Calvet 2008). Even among the more pious or orthodox sectors of the community, this commitment is also largely shared as exemplified by the practices of various private Muslim schools (Sawaf and Abu Hijleh 2008).…”
Section: Toward Mutual Adaptationmentioning
confidence: 98%
“…Numerous studies in Canada and abroad have shown that a close relationship between families and schools is beneficial to students (Deslande, 2006;Henderson &Mapp, 2002;Sheldon & Epstein, 2004). This relationship has the power to facilitate students' adaptation to school, improve their academic outcomes, diminish absenteeism, improve behavior, increase higher adolescent autonomy, and increase academic aspirations (Kanouté & Calvet, 2008;Larivée, 2011;Suarez-Orozco, 2010). There are numerous types of collaborations and parent-involvement initiatives, but the impact of these collaborations on children's academic success remains unclear (Larivée, 2011;Vatz Laaroussi et al, 2005).…”
Section: School-family-community Collaboration: An Alternative Approachmentioning
confidence: 99%
“…Plusieurs auteurs (Chen et Gregory, 2010;Deslandes, 2009;Fantuzzo et coll., 2013) reconnaissaient le modèle d'Epstein comme une assise théorique incontournable, bien que d'autres chercheurs (Jeynes, 2007(Jeynes, , 2012) mentionnent que ce modèle est simpliste. Au niveau de l'opérationnalisation du construit, le nombre de dimensions fluctue d'une étude à l'autre (Chen et Gregory, 2010;Fan et coll., 2012;Fantuzzo, Tighe et Childs, 2000;Kanouté et Calvet, 2008;Larivée, 2011). La littérature fait état de plusieurs modèles.…”
Section: What Are the Links Between Parental Involvement Familyunclassified